NILAI EDUKATIF DALAM PEMBACAAN BURDAH (STUDI ATAS PROSESI PERNIKAHAN ETNIS ARAB DI GORONTALO) - Arif, Muh. (Jurnal Studi Agama dan Masyarakat, 2020)
This article elaborated on the educational value of Burdah reading in Gorontalo and described the implementation of Burdah reading tradition in Gorontalo, where various activities were usually carried out, for example at assemblies or at the stages before wedding ceremony. In general, the indigenous people of Gorontalo, in the traditional stages before their wedding, only performed the Saronde dance after holding recitation. This was different from Arabian ethnic in Gorontalo. They preferred to read Burdah and Barzanji. The results showed that the reading of Burdah was one of the traditions carried out with a traditional pattern and was upheld by the people of Gorontalo, especially the Arab ethnic group. This was because that the Arabian ethnic people of Gorontalo made Burdah as a tradition that should not be abandoned in every ceremony, especially in wedding ceremonies, circumcision, and the Prophet's birthday. Likewise with other activities, for example when a family was suffering from a disease in the hope that they could get a cure. The educational values in reading Burdah included: first, the cultural value of Burdah tradition was implemented in the form of religious teaching through customary traditions; second, religious values in the tradition of Burdah reading contained religious teachings to strengthen faith and piety; third, the social value of the tradition of Burdah reading was in a form of religious teaching to familiarize each other with maintaining friendship, respecting and remaining united in Islamic brotherhood.